FABRIC NON-ELASTIC PULMONARY RESISTANCE IN CASE OF BRONCHIAL ASTHMA AND GOLD: DISTINCTION AND CHANGES NATURE - T. S. Ageyeva; F. F. Tetenev; A. V. Dubodelova (Бюллетень сибирской медицины)
The integral and regional values tissues of non-elastic resistance lungs (NERLi, NERLr) in 17 patients with bronchial asthma (BA), 25 – chronic obstructive pulmonary disease (COPD) and 30 healthy volunteers are investigated by means of simultaneous recording of zonal reogrammes of ventilation and transpulmonal pressure.The increase of NERLi in patients with BA is accompanied by the increase of the NERLr values inhaling in the lower zones, and exhale in the middle and lower areas of both lungs. Significant increase of NERLi In COPD accompanied by the increase of the NERLr values on the exhalation in the middle and lower areas of the right lung. And values of NERLr in BA almost 2.5 times higher than the similar values in patients with COPD. Apparently, in BA is due to an increase in the permeability of the alveolar-capillary membrane in connection with an immune inflammation, and in COPD – effect of other factors, among which the actual tissue friction and reducing of mechanical activity light to overcome the total resistance.